Crossfire trail - Kane, Thomas; Brandman, Steven; Wincer, Simon; Selleck, Tom, 1945-; Madsen, Virginia, 1961-; Brimley, Wilford, 1934-2020.; Johnson, Brad, 1959-; Harmon, Mark, 1951-; L'Amour, Louis, 1908-1988.; Turner Network Television; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2001)
A restless wanderer is bound by a promise to watch after the widow of a dying friend. His vow leads him to a small town terrorized by a saloon owner and his hired gunman.
Based on the novel by Louis L'Amour ; originally broadcast on cable television in 2001.
Director of photography, David Eggby ; editor, Terry Blythe ; music, Eric Colvin ; costume designer, Elsa Zamparelli ; production designer, Roy Forge Smith.
Tom Selleck, Virginia Madsen, Wilford Brimley, Brad Johnson, Mark Harmon.
DVD ; region 1 ; widescreen presentation ; Dolby surround stereo.
Closed-captioned; English dialogue with English and French subtitles.
110063
Keywords: 1800-1899; Cowboys -- Wyoming -- Drama; Frontier and pioneer life -- Wyoming -- Drama; Wyoming -- History -- 19th century -- Drama; Video recordings for the hearing impaired; Drama; Film adaptations; Made-for-TV movies; History; Fiction television programs; Western television programs; French language materials -- Bilingual